Odpowiedź :
20-3x=2x+5
-3x-2x=5-20
-5x=-15 /:(-5)
x=3
3(x-2)-7=8
3x-6-7=8
3x=8+6+7
3x=21 /:3
x=7
2-(5+x)=2(3-x)
2-5-x=6-2x
-x+2x=6-2+5
x=9
-3x-2x=5-20
-5x=-15 /:(-5)
x=3
3(x-2)-7=8
3x-6-7=8
3x=8+6+7
3x=21 /:3
x=7
2-(5+x)=2(3-x)
2-5-x=6-2x
-x+2x=6-2+5
x=9
Cześć!
Szczegółowe wyjaśnienie:
a)
[tex]20 - 3x = 2x + 5 \\ - 3x - 2x = 5 - 20 \\ - 5x = - 15 | \div - 5 \\ \underline{x = 3}[/tex]
b)
[tex]3(x - 2) - 7 = 8 \\ 3x - 6 - 7 = 8 \\ 3x - 13 = 8 \\ 3x = 8 + 13 \\ 3x = 21 | \div 3 \\ \underline{x = 7}[/tex]
c)
[tex]2 - (5 + x) = 2(3 - x) \\ 2 - 5 - x = 6 - 2x \\ - 3 - x = 6 - 2x \\ - x + 2x = 6 + 3 \\ \underline{x = 9}[/tex]